Otimização de processos em indústria têxtil - Oliveira, Eduardo Alves de (2013)
In this work it was developed a multi-objective optimization model for the production planning of an industrial laundry. The model allows better leverage energy resources and capabilities of the installed equipment as well as reduces process costs, considering the constraints of the system. The model is based on the classical methods of process selection and lot sizing. A real industrial process was used as a case study to test the applicability of the proposed model. The study was developed in a laundry in Maringá, State of Paraná, which is one of the largest manufacturing centers of Brazil. The study was conducted in the drying stage, distributing in ten dryers with lots of different sizes and power consumption. It was considered periods of one hour for each dryer, of twenty-one hours of daily work and twenty-six days in the month, including all three shifts. Besides the application of the model it was also possible to identify flaws in the process, including waste of capacity and misuse of equipment. Through the study it was possible to establish plans for efficient production and optimal allocation of resources in each of the steps. The achieved overall contribution margin was better than the current margin adopted by the laundry for the study period, and can be applied in all other months of the year.